The role of institutional investors in improving board of director attributes around the world - Badar Alshabibi (Journal of Risk and Financial Management, 2021)
This paper investigates the role of institutional investors in the improvement of corporate governance for the companies in which they invest (investee companies) using evidence about the attributes of boards of directors across 15 countries. Furthermore, this paper examines the extent to which the activism of institutional investors is determined by the institutional environment, to include various economic conditions (pre-crisis, crisis and post-crisis), legal systems and ownership structures. Drawing from the agency theory and institutional theory, the results show that foreign institutional investors are the main promoters of board governance structures across the globe. This study also provides evidence that institutional investors promote the independence of a board and its audit and compensation sub-committees (but excluding its nomination committee). The study also demonstrates that institutional investors reduce board entrenchment, though it presents no evidence that institutional investors reduce board busyness. The results also suggest that institutional investors behave differently when operating within different economic conditions (pre-crisis, crisis and post-crisis), legal systems and ownership structures. This paper contributes to the growing literature on shareholder activism and comparative corporate governance mechanisms. The findings suggest that the activism of institutional investors is contingent on the institutional settings, to include economic conditions, legal systems and ownership structures.
Keywords: 330; corporate governance; board of directors' mechanisms; institutional settings; institutional shareholder; shareholder activism